2006
DOI: 10.1002/adma.200502051
|View full text |Cite
|
Sign up to set email alerts
|

Polymer‐Relief Microstructures by Inkjet Etching

Abstract: Polymer microstructures are prepared by inkjet etching. By varying the distance between the printed solvent droplets, rectangular and honeycomb hole arrays like those shown in the figure are formed. These holes can act as reservoirs for other inkjet‐printed materials, such as quantum dots. The technique holds promise for rapid‐ prototyping applications and microarray fabrication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
55
0
3

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 21 publications
0
55
0
3
Order By: Relevance
“…Although this method of via hole formation relies on the wetting and evaporation characteristics of the droplet on the polymer substrate and the rate of dissolution of polymer into the solvent, the size of the via hole is primarily determined by the volume of the droplet impacting on the substrate [14,24]. Accordingly one can expect that the droplet ejection frequency will influence the diameter of the via holes created if the frequency is high enough for incomplete droplet evaporation to occur between impacts.…”
Section: Introductionmentioning
confidence: 99%
“…Although this method of via hole formation relies on the wetting and evaporation characteristics of the droplet on the polymer substrate and the rate of dissolution of polymer into the solvent, the size of the via hole is primarily determined by the volume of the droplet impacting on the substrate [14,24]. Accordingly one can expect that the droplet ejection frequency will influence the diameter of the via holes created if the frequency is high enough for incomplete droplet evaporation to occur between impacts.…”
Section: Introductionmentioning
confidence: 99%
“…Kawase et al 15,16 etched via holes in a polymer dielectric layer for interconnection using inkjet printing for making all plastic transistor circuits, owing to the coffee ring effect, during which materials loaded in solvents are carried to the contact line. 16,20,21,23,24 Few have studied the limitation of using inkjet etching to produce via holes in polymer layers. Via hole formation in polymer films by inkjet etching is through polymer dissolution and re-deposition, which is different from etching holes in silicon dioxide reported by Lennon et al, 25 where chemical reaction is involved and the soluble product can be washed away afterwards in water.…”
Section: Related Articlesmentioning
confidence: 99%
“…Kawase et al 15,16 etched via holes in a polymer dielectric layer for interconnection using inkjet printing for making all plastic transistor circuits, owing to the coffee ring effect, during which materials loaded in solvents are carried to the contact line. [17][18][19] de Gans et al 20,21 demonstrated arrays of holes of different shapes in polystyrene using inkjet-printed drops. Xia and Friend 4,22 observed a thin polymer layer at the bottom of these holes after solvent evaporation and reported its removal by continuous solvent deposition.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Inkjet, as a digitally driven and non-contact printing method, has been used for various electronics manufacturing applications, such as transistor and organic light-emitting diode (OLED) fabrication, [1][2][3][4][5] polymer structural patterning, [6][7][8][9][10][11][12] microlenses, [13][14][15] and other fields over the last decade as printed electronics has attracted great interest both in academia and in industrial application. One recently emerged investigation is the use of inkjet printing as a subtractive etching process rather than an additive manufacturing technique, which is what inkjet printing is usually utilized for.…”
mentioning
confidence: 99%